H2A.Z.1 Monoubiquitylation Antagonizes BRD2 to Maintain Poised Chromatin in ESCs - Lauren E. Surface; Paul A. Fields; Vidya Subramanian; Russell Behmer; Namrata Udeshi; Sally E. Peach; Steven A. Carr; Jacob D. Jaffe; Laurie A. Boyer (Cell Reports, 2016)
Summary: Histone variant H2A.Z occupies the promoters of active and poised, bivalent genes in embryonic stem cells (ESCs) to regulate developmental programs, yet how it contributes to these contrasting states is poorly understood. Here, we investigate the function of H2A.Z.1 monoubiquitylation (H2A.Z.1ub) by mutation of the PRC1 target residues (H2A.Z.1K3R3). We show that H2A.Z.1K3R3 is properly incorporated at target promoters in murine ESCs (mESCs), but loss of monoubiquitylation leads to de-repression of bivalent genes, loss of Polycomb binding, and faulty lineage commitment. Using quantitative proteomics, we find that tandem bromodomain proteins, including the BET family member BRD2, are enriched in H2A.Z.1 chromatin. We further show that BRD2 is gained at de-repressed promoters in H2A.Z.1K3R3 mESCs, whereas BRD2 inhibition restores gene silencing at these sites. Together, our study reveals an antagonistic relationship between H2A.Z.1ub and BRD2 to regulate the transcriptional balance at bivalent genes to enable proper execution of developmental programs. : Shedding light on the contrasting functions of the histone variant H2A.Z.1 in gene regulation, Surface et al. show that H2A.Z.1 monoubiquitylation is required for the transcriptional repression of developmental promoters in mESCs by antagonizing downstream transcriptional activators including the BET bromodomain family member BRD2.